2017
DOI: 10.1371/journal.pone.0177835
|View full text |Cite
|
Sign up to set email alerts
|

Total hip/knee arthroplasty in the treatment of tumor-induced osteomalacia patients: More than 1 year follow-up

Abstract: BackgroundTumor-induced osteomalacia (TIO) may result in a better prognosis after complete resection of the causative neoplasm. However, tumors located proximal to the articular surface of the metaphysis remain largely uninvestigated.MethodsA retrospective study of sixteen patients was undertaken to evaluate treatment of tumors with joint arthroplasty and tumor resection. The bone metabolism index, hip/knee joint function, arthroplasty complications and symptoms were followed up for at least 12 months in each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Considering the residual seeding of the tumor, we chose hemiarthroplasty, as we decided that a total hip arthroplasty with manipulation on the acetabular side would be risky. However, given that a report of total hip and knee replacements for TIO showed good results in all the cases, and if the concerns of seeding and invasiveness could be dispelled, it might have been considered as an option [ 8 ]. In the present case, the surgical outcome proved to be effective, and the patient remained in biochemical remission, albeit for a short period of time.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the residual seeding of the tumor, we chose hemiarthroplasty, as we decided that a total hip arthroplasty with manipulation on the acetabular side would be risky. However, given that a report of total hip and knee replacements for TIO showed good results in all the cases, and if the concerns of seeding and invasiveness could be dispelled, it might have been considered as an option [ 8 ]. In the present case, the surgical outcome proved to be effective, and the patient remained in biochemical remission, albeit for a short period of time.…”
Section: Discussionmentioning
confidence: 99%
“…Further results showed that joint replacement and tumor resection can significantly and quickly improve bone metabolism indicators in TIO patients, without tumor recurrence during short-term follow-up [57] . Also, the postoperative joint function score of the patients was significantly improved [57] . The major postoperative complications in these patients mainly included postoperative pain, joint clicking, and secondary hyperparathyroidism [57] .…”
Section: Principles and Methods Of Orthopedic Surgical Treatmentmentioning
confidence: 89%
“…Moreover, joint replacement surgery is suitable for patients whose tumor cannot be completely removed since it may result in persistent symptoms [57] . Zhu et al [57] conducted a retrospective study with 16 TIO patients to evaluate the surgical treatment effect of joint replacement and tumor resection on PMTs and found that causative tumors were located on the metaphyseal joint surface after a one-year postoperative follow-up of bone metabolism index, hip/knee joint function, joint replacement complications, and symptoms. Thirteen cases were undergoing hip joint replacement, and three cases were undergoing knee joint replacement [57] .…”
Section: Principles and Methods Of Orthopedic Surgical Treatmentmentioning
confidence: 99%
See 2 more Smart Citations